Canine corneoconjunctival hemangiosarcoma: case report from Costa Rica - Bermúdez-Jiménez, Eugenia (2024)
A 10-year-old, 8-month-old indoor, outdoor male mixed breed dog had a dark red nodule on the left cornea. Treatment included surgical removal of tissues from the temporal corneoconjunctival area, cryotherapy, and graft placement. The dog was diagnosed with hemangiosarcoma by histopathology. One year and two months after surgery, the eye is functional and shows no signs of tumor regrowth.